Traditional Chinese medicine and sports drug testing: identification of natural steroid administration in doping control urine samples resulting from musk (pod) extracts - Thevis, M.; Schänzer, W.; Geyer, H.; Thieme, D.; Grosse, J.; Rautenberg, C.; Flenker, U.; Beuck, S.; Thomas, A.; Holland, R.; Dvorak, J. (British Journal of Sports Medicine, 2013)
The administration of musk extract, that is, ingredients obtained by extraction of the liquid secreted from the preputial gland or resulting grains of the male musk deer (eg, Moschus moschiferus), has been recommended in Traditional Chinese Medicine (TCM) applications and was listed in the Japanese pharmacopoeia for various indications requiring cardiovascular stimulation, anti-inflammatory medication or androgenic hormone therapy. Numerous steroidal components including cholesterol, 5a-androstane-3,17-dione, 5ß-androstane-3,17-dione, androsterone, etiocholanolone, epiandrosterone, 3ß-hydroxy-androst-5-en-17-one, androst-4-ene-3,17-dione and the corresponding urea adduct 3a-ureido-androst-4-en-17-one were characterised as natural ingredients of musk over several decades, implicating an issue concerning doping controls if used for the treatment of elite athletes. In the present study, the impact of musk extract administration on sports drug testing results of five females competing in an international sporting event is reported. In the course of routine doping controls, adverse analytical findings concerning the athletes' steroid profile, corroborated by isotope-ratio mass spectrometry (IRMS) data, were obtained. The athletes' medical advisors admitted the prescription of TCM-based musk pod preparations and provided musk pod samples for comparison purposes to clarify the antidoping rule violation. Steroid profiles, IRMS results, literature data and a musk sample obtained from a living musk deer of a local zoo conclusively demonstrated the use of musk pod extracts in all cases which, however, represented a doping offence as prohibited anabolic-androgenic steroids were administered.